1982
DOI: 10.3382/ps.0611734
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of the Turkey Hen as Affected by Initial Insemination and Onset of Egg Production

Abstract: A comparison between initial inseminations of Large White turkey hens prior to or after onset of egg production was undertaken to determine the effect on fertility. Semen from Bronze toms was utilized for the initial inseminations whereas all subsequent inseminations utilized White sires. After 10 weeks there were no significant differences between treatments for percent egg production or hatchability. Inseminating prior to the onset of egg production resulted in a significantly different (P less than or equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

1986
1986
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 6 publications
1
4
1
Order By: Relevance
“…This is consistent with previous reports by Mclntyre et al (1982) and Mclntyre and Christensen (1986).…”
Section: Resultssupporting
confidence: 95%
See 2 more Smart Citations
“…This is consistent with previous reports by Mclntyre et al (1982) and Mclntyre and Christensen (1986).…”
Section: Resultssupporting
confidence: 95%
“…Fertile eggs of the EI treatments hatched significantly better than fertile eggs of the LI treatments. This has not been observed in previous studies (Mclntyre et al, 1982;Mclntyre and Christensen, 1985). Furthermore, eggs from the 20 million sperm/AI group The hatch of fertile eggs for the 20, 50, and 100 million sperm/AI groups in Weeks 16 to 20 was 56.6, 72.6, and 67.0%, respectively, with the 20 million group being significantly lower than the other two.…”
Section: Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…Artificial insemination (AI) of turkey hens before the onset of egg production generally results in higher hen fertility than in hens inseminated initially after the onset of egg production (Mclntyre et al, 1982(Mclntyre et al, , 1986. Although the physiological basis of these observations has not been established, Mclntyre et al (1982) suggested that there is "... an increased receptiveness of the hen's oviduct to spermatozoa during the time that natural mating frequency is highest".…”
Section: Introductionmentioning
confidence: 95%
“…Although the physiological basis of these observations has not been established, Mclntyre et al (1982) suggested that there is "... an increased receptiveness of the hen's oviduct to spermatozoa during the time that natural mating frequency is highest".…”
Section: Introductionmentioning
confidence: 99%